International Dimension in Colonization of the North-West of America and California at the End of the 17-18 th Centuries - A. Y. Petrov; V. N. Kostornichenko; M. M. Koskina (Vestnik MGIMO-Universiteta)
The article reviews the initial period of European colonization of the North Pacific Ocean and California within the context of diplomatic relations between Russia and Spain during the late 17th and early 18th centuries. It tries to understand the policies of European powers in the American Northwest and the reasons for pursuing their colonial interests there. It analyses the history of exploration of these territories, expeditions to the northern part of the Pacific Ocean, and historical maps of this region. For the first time in Russian historiography the authors touch upon the exploration of California in the 18th century.The exploration of the North Pacific Ocean, the northwestern American coast, including certain areas of California, Alaska and the Aleutian Islands has long attracted the attention of European powers. It was a process in which government authorities and private merchant companies took part. The expansion of the Spanish Empire into California was made possible in part because of the concerns of the Madrid court about the strengthening of the Russian and British empires in the North Pacific Ocean. The Spanish documents from the archives of Madrid, Seville and Simancas – the article introduces them into research communication the first time - show the validity of the fears of the Madrid court regarding the inevitable development of Russian colonization in the region. The advance of Russia to the shores of America has economic reasons: Cossacks and merchants reached the Pacific Ocean pursuing the desire to profit from the fur trade. As the economic influence expanded, the state interests of annexing territories and bringing the local population into citizenship followed behind. The territorial advance of the Russians to the Pacific Ocean was facilitated by the ambitious, but at the same time balanced diplomacy of Peter I, which managed to ensure the expansion of the borders of the Russian Empire.Spanish consolidation in certain territories in California was aimed at a possible containment of the Russian advance. Russian-Spanish relations in the Northwest Pacific at the end of the 17th – 18th centuries contributed to the nature of the subsequent development of territories in the North Pacific Ocean.